Reputational risks management and mitigation: Empirical evidence from the wedding organizer sector - Iskandar, Bayu; Maarif, Syamsul; Ramadyanto, Widodo (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
Purpose – The purpose of this research is to identify and determine reputation risk mitigation strategies that may arise in the business processes of wedding activities at Lifetime Organizer Bogor. A poor reputation for a wedding organizer can drive consumers to switch to competitors with a better reputation. Therefore, effective reputation risk management is crucial for wedding organizers.Design/methodology/approach – This study employs the Risk Assessment Godfrey method and Flanagan & Norman Risk Response Analysis. Risks are identified through direct observation at multiple weddings organized by Lifetime Organizer, in-depth interviews with the owner and field coordinators, and the distribution of questionnaires to partner vendors and consumers of Lifetime Organizer. The risk assessment is calculated using a comprehensive approach that combines qualitative and quantitative elements, facilitated by questionnaires, and processed through geometric mean calculations.Findings – The findings in this study contain mitigation action strategies for risks with high and extreme risk levels. These mitigation strategies are organized based on implementation that aligns with the company's needs and resources, thereby enabling the company to proactively prevent the occurrence of such risks.Research limitations/implications – In this study, the identified risks pertain to factors that may influence the company's reputation. Since reputation is a subjective perception held by individuals, it introduces subjectivity in the process of identifying and evaluating risks. It is anticipated that in future research endeavors, this aspect will be duly considered and addressed.Practical implications – The research holds significant practical implications for wedding organizers, providing a tailored approach to reputation risk management. The proposed strategies, informed by the risk assessment framework, empower companies to navigate the dynamic event planning industry effectively, fostering long-term success and resilience.Originality/value – This study contributes novelty by adapting and applying established risk assessment methods to the specific context of the wedding planning industry in Indonesia. The findings offer a unique perspective on reputation risk management, providing valuable insights for both industry practitioners and researchers in developing countries.